Diabetaksi: Aksi Sehat Komunitas Lawan Diabetes Pada Posbindu Teratai di Wilayah Cinere - Bella, Syarla; Cinta, Azzahra; Arafah, Nathaniella; Latipah, Tatu; Afifah, Laili; Evilia, Stella; Khairunnisa, Cintia Zahwa (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Health education on diabetes mellitus (DM) is crucial for residents, given the increasing prevalence of the disease among young people. This article discusses the implementation of a diabetes education program at Posbindu Teratai as an early prevention effort against diabetes risk. The program aims to provide residents with a comprehensive understanding of diabetes, risk factors, symptoms, and prevention methods that can be applied in everyday life. The methods used are interactive lectures, group discussions, and practical activities that involve residents directly, thus creating an active learning environment. The results of the pre-test and post-test showed a significant increase in residents' knowledge about diabetes after participating in this education. In addition, the students' response to the materials provided was very positive, especially regarding the importance of a healthy diet, regular exercise, and early detection of diabetes symptoms. This program is expected to create a younger generation that is more health-conscious and can spread diabetes prevention information in their neighborhoods. In conclusion, this diabetes education program is effective in increasing the knowledge and awareness of residents about the importance of diabetes prevention.